Metode Nilai Harapan dan Nilai Kesempatan yang Hilang sebagai Alat Pengambilan Keputusan dalam Kondisi Risiko - Endro Prihastono (Jurnal Ilmiah Dinamika Teknik, 2008)
In decision making it is necessary to have thorough information, if the informalion isn complete, or the data are bared on assumption only, the decision maker will not be able to decide anything for sure. For this purpose there must be a probability concept in order to comply with future consequences. Decision making involves impregnable aspects such as reaction to competitors and inflation index which can influence the organizational finance. One of the decision making conditions is risk condition. There are two criteria in such a condition i.e. Expected pay off and Opportunity loss both criteria will give consistent pay off meaning that the use of expected pay off method has been used to make the best decision. There fore both method (Expected pay off and Opportunity loss) turn out to he effective resulting in the some outcome